A review of alternative intravenous acetylcysteine regimens for acetaminophen overdose. Issue 10 (3rd October 2021) - Burnham, Kevin; Yang, Tianrui; Smith, Haleigh; Knight, Steven
ABSTRACT: Introduction: Acetylcysteine is the standard treatment for preventing hepatotoxicity caused by acetaminophen overdose. Several novel approaches to the management of acetaminophen overdose have been suggested to improve patient safety by reducing adverse drug reactions and dosing errors. This article reviews these alternative treatment regimens and intends to offer a detailed assessment of the available options to assist providers in managing cases of acetaminophen overdose. Areas covered: This review article covers observational and experimental studies that assessed the efficacy and safety of alternative intravenous acetylcysteine regimens for acetaminophen overdose. A literature search was conducted using PubMed, ProQuest, and Scopus to identify the studies, which included results through April 2021. The assessment of alternative regimens consists of a discussion on the limitations and benefits, barriers to implementation, and important considerations for each regimen. Expert opinion: Several alternative regimens have been studied and implemented in various institutions. Many of these dosing regimens have supporting safety data but most lack robust data. A reduction in infusion-related side effects is an important outcome, but established efficacy, local poison center familiarity with the regimen, institutional resources, and patient-specific factors should be equally considered when deciding on implementing and using an alternative dosing strategy.